'Let's be Still': A school psychologist delivered stillness meditation program for wellbeing. Issue 2 (9th December 2021) - Yerbury, Rachel
Abstract: School counsellors implement preventative programs to build student resilience and coping skills to counteract the rising mental health needs of children in Australia. School-based meditation programs are effective for individuals and groups, with documented benefits. Most literature examines mindfulness meditation, and the current, exploratory study aimed to add to the research breadth by considering stillness meditation. The stillness program 'Let's be Still' is a 10-week, class-based program that was conducted between 2015–2020 by the school psychologist in a regional, independent New South Wales school. Data were collected from questionnaire responses of 169 Year 2 (7–9 years) and five teachers to document what the children had learnt and how it helped them. Thematic analysis of the responses revealed an emphasis on stillness promoting positive emotions and behaviours. Both students and teachers articulated that learning and practising stillness provided the students with tools to be calm, relaxed and settled, to deal with conflict and to have a break from the busyness of the school day. While the study design does not allow generalisability of the program's effectiveness, this study may offer input for school counsellors considering the implementation of a school-based meditation program.